System Reliability Assessment Based on Failure Propagation Processes. (26th June 2018) - Lin, Shuai; Wang, Yanhui; Jia, Limin
Abstract : One or several component failures may lead to more related component malfunction and ultimately cause system reliability reduction. Based on this, we focus on the assessment system reliability of complex electromechanical systems (CEMSs) in a fault-propagation view. First, failure propagation model taking into consideration failure data based on network theory and improved polychromatic sets is proposed for system reliability evaluation. From the node point of view, system effectiveness index is constructed to investigate the variation of efficiency of the holistic network. Subsequently, from the system's perspective, system reliability measurement is provided and estimated in combination with system effectiveness index and failure propagation models. Finally, the application of proposed method to a bogie system of high-speed train assesses system reliability, and meanwhile, the effectiveness of the proposed method is able to be illustrated.